(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study religious education management of monks in Buddhism, 2) to study religious education management of monks in Udon Thani Province, and 3) to propose the model of religious education management of monks in Udon Thani Province. This research was qualitative research. The data were collected from primary sources and secondary sources and interview. The descriptive analysis was used to analyze. Results found that for religious education management of monks in Buddhism, it aimed to Sikkha (the threefold learning) in the Buddha era. Buddha’s doctrine was said that it was the principle of the conduct and Buddhism dissemination. Later, it was divided into Gantha-dhura (burden of study) and Vipassana-dhura (burden of insight development). Since Buddhism has been spread to Thailand, religious education management of monks has evolved respectively to the present. Religious education management was divided into Dhamma division, Pali division and general education division. Religious education management of monks in Udon Thani province could be divided into three divisions 1) Dhamma Studies consisting of Dhamma curriculum and Dhamma studies, Sunday Buddhism curriculum, 2) Pali division consisting of Pali curriculum and Pali studies. The measurement and evaluation are in accordance with the Sanam Luang national Dhamma studies-Pali studies. 3) Phrapariyattidhamma general education division. The curriculum is in accordance with Ministry of Education. The model of religious education management of monks in Udon Thani province, Dhamma division and Pali division should have a short curriculum for monks and lay people. Teaching should be taught through online. The measurement and evaluation should have retest for Dhamma, and general education division should organize curriculum for lay people to learn in the class. Vocational curriculum should be provided. Teachers should be appointed as regular instructor and provided welfare, and supported scholarship for higher education.